Acute efficacy of contiguous versus temporally discontiguous point-by-point radiofrequency pulmonary vein isolation in patients with paroxysmal atrial fibrillation: a randomized study - Aldhoon, Bashar; Peichl, Petr; Osmančík, Pavel; Konečný, Petr; Kautzner, Josef; Wichterle, Dan (Journal of interventional cardiac electrophysiology, 2022)
PURPOSE: Durable pulmonary vein (PV) isolation (PVI) determines the clinical success of catheter ablation for atrial fibrillation. In this randomized study, we investigated whether the temporally discontiguous deployment of ablation lesions adversely affected the acute efficacy of PVI. METHODS: Thirty-six consecutive patients with drug-refractory paroxysmal atrial fibrillation (aged 59 ± 11, 58% males) were randomized 1:1 to either discontiguous (D-PVI) or contiguous (C-PVI) encircling radiofrequency (RF) lesions around ipsilateral PVs. A contact force-sensing catheter was used targeting a final interlesion distance < 6 mm and the ablation index of 400-450 (anterior wall) and 300-350 (posterior wall). The study endpoint was defined as failure of first-pass PVI or acute PV reconnection during a waiting time (> 30 min) followed by adenosine challenge. RESULTS: The total RF time, number of RF lesions, and mean interlesion distance were comparable in both groups. Total endpoint rates were 1/36 (3%) in the D-PVI vs 4/36 (11%) in the C-PVI groups; P = 0.34 for superiority, P = 0.008 for non-inferiority. Adenosine-induced reconnection of right PVs was the only endpoint in the D-PVI group. In the C-PVI group, first-pass PVI failed in 2 right PVs and spontaneous reconnection occurred in 2 other circles (left and right PVs). CONCLUSION: Temporally discontiguous deployment of RF lesions is not associated with lower procedural PVI efficacy when strict criteria for interlesion distance and ablation index are applied. The development of local edema around each ablation site does not prevent effective RF lesion formation at adjacent positions. TRIAL REGISTRATION: clinicaltrials.gov (NCT03332862).
Keywords: Catheter Ablation; adenosin; Recurrence; fibrilace síní; Adenosine; lidé; Female; mužské pohlaví; Male; recidiva; Atrial Fibrillation; katetrizační ablace; Pulmonary Veins; Treatment Outcome; venae pulmonales; výsledek terapie; ženské pohlaví; Humans